(untitled) (Indian Journal of Animal Production and Management, 2015)
The effect of zinc and copper ratio on body weight gain was studied on 24 healthy crossbred (Hampshire ´ Assam local) male piglets with similar body weight at 2 months of age which were randomly divided into four groups, viz., Control T1, T2 and T3 comprising of 6 piglets in each group. The ratio of zinc and copper supplementation was done to different groups as for T1 – 125:12.5 ppm; T2 – 150:15 ppm and T3 – 175 : 17.5 ppm. The piglets were kept under intensive system of rearing following all the managemental practices in the farm belonging to AICRP on Pig, College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati-22. Body weight of each animal of respective groups was measured and blood samples were collected at fifteen days interval beginning from 2 months upto 6 months of age. Serum was separated and stored at -20oC for hormonal estimation. The body weight in all four groups during the trial period clearly revealed that there was gradual increase in the body weight of pigs which was highest (52.70 ± 0.69 kg) in T3 and lowest (42.90 ± 0.32 kg) in control group. The serum zinc concentration in all four groups during the trial period revealed apparent increase with the highest (0.30 ± 0.03 ppm) in T3 and lowest (0.26 ± 0.03 ppm) in control group. The serum copper concentration was highest 0.25 ± 0.01 ppm) in T3 and lowest (0.21 ± 0.01 ppm) in control group. During the experimental period, there observed a linear increasing trend of serum copper concentration in general irrespective of groups. Supplementation of zinc and copper at 175 ppm: 17.5 ppm per day was found to be beneficial with highest growth.